Towards symbiocene. The future of climate education in Poland - Bała, Adam; Ochwat, Magdalena; Skubała, Piotr (No Limits, 2024)
Schools need to teach about what is happening to our planet and reflect critically on the ways in which Homo sapiens has been inhabiting it based on destruction, extraction, and exploitation. The degradation of the environment will not leave the morality, sensitivity, and imagination of the youngest generation unaffected, and we will all feel its consequences. Therefore, schools have the duty to prepare students for the inevitable.